Downregulation of NAGLU in VEC Increases Abnormal Accumulation of Lysosomes and Represents a Predictive Biomarker in Early Atherosclerosis - Xing, Changchang; Jiang, Zhongyi; Wang, Yi (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs), predominantly caused by atherosclerosis (AS), is the leading cause of mortality in the world. Despite the fact that a great number of previous studies attempted to reveal the molecular mechanism of AS, the underlying mechanism has not been fully elucidated. The aberrant expression profiling of vascular endothelial cells (VECs) gene in early atherosclerosis (EAS) was analyzed according to the dataset (GSE132651) downloaded from the Gene Expression Omnibus (GEO) database. We primarily performed functional annotation analysis on the downregulated genes (DRGs). We further identified that α-N-Acetylglucosaminidase (NAGLU), one of the DRGs, played a critical role in the progression of EAS. NAGLU is a key enzyme for the degradation of heparan sulfate (HS), and its deficiency could cause lysosomal accumulation and lead to dysfunctions of VECs. We found that siRNA knockdown of NAGLU in human umbilical vein endothelial cell (HUVEC) aggravated the abnormal accumulation of lysosomes and HS. In addition, the expression of NAGLU was reduced in the EAS model constructed by ApoE-/- mice. Furthermore, we also showed that heparin-binding EGF-like growth factor (HB-EGF) protein was upregulated while NAGLU knockdown in HUVEC, which could specifically bind to vascular endothelial growth factor receptor 2 (VEGFR2) and promote its phosphorylation, ultimately activating the phosphorylation levels of extracellular signal-regulated kinases (ERKs). However, the applications of selective VEGFR2 and ERKs inhibitors, SU5614 and PD98059 respectively, could reverse the abnormal lysosomal storage caused by NAGLU knockdown. These results implicated that downregulation of NAGLU in HUVEC increases abnormal accumulation of lysosomes, and maybe a potential biomarker for the diagnosis of EAS.